Comprehensive bioinformatic profiling of matrix metalloproteinases and their inhibitors: Expression and interaction patterns in head and neck cancer toward predictive biomarkers and personalized therapies - Rishaba Byju; Sredha Sunil; Sabari Sadhasivan; Rajesh Parsanathan (Oral Oncology Reports)
Objective: Matrix metalloproteinases (MMPs) and Tissue inhibitors of metalloproteinases (TIMPs) are involved in the turnover of extracellular matrix (ECM) components. Overexpression of MMPs facilitates tumour progression by promoting ECM turnover, angiogenesis, and cell migration. Head and neck squamous cell carcinoma (HNSCC) exhibits significant upregulation of multiple MMPs and TIMPs, correlating with poor prognosis, using bioinformatics tools to analyse the expression profiles and prognostic significance of MMPs and TIMPs in HNSCC. Materials and methods: GEPIA and UALCAN databases were used to analyse the expression of MMPs and TIMPs in HNSCC tissues. Immunohistochemistry confirmed high protein levels of several MMPs in tumour samples. GeneMANIA, STRING, and Metascape analyses highlighted key functional relationships and pathways enriched in MMPs and TIMPs. Kaplan-Meier survival analyses were conducted to assess the prognostic significance of TIMPs in HNSCC. Results: The study found significant overexpression of MMP1, MMP2, MMP3, MMP9, and MMP14 in HNSCC tissues. Immunohistochemistry confirmed elevated protein levels of these MMPs in tumour samples. PPI network analyses indicated crucial interactions among MMPs and their regulatory pathways. TIMP1 was significantly upregulated in HNSCC, while TIMP3 downregulation correlated with increased MMP activity and tumour progression. According to Kaplan-Meier survival analyses, higher TIMP expression was associated with poor overall survival in HNSCC patients. Conclusion: This comprehensive study emphasises the dysregulation of MMPs and TIMPs in HNSCC, proposing them as potential biomarkers for early diagnosis and prognostic evaluation and suggesting them as therapeutic targets to improve clinical outcomes in HNSCC patients.